Raman modes and dielectric relaxation properties of epitaxial BaBiO3 thin films. (13th January 2020) - Talha, M; Lee, Y W
Abstract: Perovskite BaBiO3 films are grown on MgO (100) substrate and SrTiO3 (001) and (110) substrates using pulsed laser deposition. The thickness of the films ranges from ∼10 nm up to 200 nm. X-ray diffraction and reciprocal space mapping show that the thin films are grown epitaxially but relaxed considerably particularly for the films on SrTiO3 . The topography of the film surfaces are obtained with AFM and found to be atomically flat with the step and terrace structure of unit cell step height. Raman spectroscopy is performed on the BaBiO3 films in the temperature range from 50 K to 300 K. The phonon modes related to octahedral breathing, bond bending, and bond stretching are detected in the Raman spectra, and the distinctive features are found in the phonon modes below and above a structural transition around 140 K. Out-of-plane dielectric measurements are also carried out from 10 K to 400 K for the films on SrTiO3 with different orientations. In particular, the dielectric measurements demonstrate frequency as well as orientation dependent anisotropic dielectric relaxation behaviors in BaBiO3 films.